(untitled) (Quinto Sol, 2022)
This article analyzes the process of transformation of the student movement of the National Workers University from its incipient training with the appearance of the Argentine Federation of Students of the Workers University during the Peronist Government, until the emergence and consolidation of the Technological University Federation in the framework of the so-called struggle for the autonomy and hierarchy of the National Technological University. Likewise, we will reconstruct what were the successive approaches between the student organization that emerged after the triumph of the self-styled liberating revolution in that university and the reformist student movement. This task will be carried out based on the analysis of various documentary sources and interviews with various actors that were part of this process.